2001
DOI: 10.1097/00001888-200104001-00010
|View full text |Cite
|
Sign up to set email alerts
|

What Did We Learn about Early Clinical Experience?

Abstract: This article explores the lessons learned by ten demonstration schools regarding the early clinical experience (ECE) component of the Interdisciplinary Generalist Curriculum (IGC) PROJECT: Students in ECE at these schools participated in longitudinal, one-to-one or two-on-one preceptorships with primary care physician preceptors in outpatient settings. Development of an ECE was a key component of curricular change at each of the IGC Project schools. Shattering the traditional barrier between preclinical and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…They are assumed to ease the transition from preclinical to clinical training (Prince et al 2000;Seabrook 2004), motivate students to learn (Prince et al 2000), and help them forge their professional identity (O'Brien et al 2001;Pitkala and Mantyranta 2003). Students have been reported to feel more comfortable performing physical examination (O'Brien et al 2001) and be more aware of the impact of illness on patients (Cooper et al 2001;Frank et al 1996) as a result of seeing real patients. A systematic review of early patient contacts cited positive effects on professional socialisation (Dornan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are assumed to ease the transition from preclinical to clinical training (Prince et al 2000;Seabrook 2004), motivate students to learn (Prince et al 2000), and help them forge their professional identity (O'Brien et al 2001;Pitkala and Mantyranta 2003). Students have been reported to feel more comfortable performing physical examination (O'Brien et al 2001) and be more aware of the impact of illness on patients (Cooper et al 2001;Frank et al 1996) as a result of seeing real patients. A systematic review of early patient contacts cited positive effects on professional socialisation (Dornan et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of early patient contacts cited positive effects on professional socialisation (Dornan et al 2006). Reported positive effects also include improved acquisition and retention of knowledge (Prince et al 2000;Seabrook 2004) and contextualisation of basic science knowledge (O'Brien et al 2001;Mann 1994) by linking real patients with theory. However, no detailed studies have addressed exactly in what way early patient contacts impact on how students acquire knowledge, use basic science knowledge and integrate basic science and clinical knowledge during clinical reasoning.…”
Section: Introductionmentioning
confidence: 99%
“…26 Students perception of advantages of ECE were that it provided important validation of the student's decision to go to medical school, it was a lifeline that helped the student stay focused on their studies and provided opportunity to establish a link between the basic sciences concepts and actual patient cases. 26,27 Faculty perception of advantages of ECE were that it provided a more integrated approach to teaching basic sciences and clinical medicine, increased excitement for learning by students, provided better comprehension of basic science knowledge.…”
Section: Educational Theory Supporting Ecementioning
confidence: 99%
“…For example, a recent study found that, at large institutions, these courses can involve as many as 1,800 community faculty members. 10 Currently, individual PCCS courses have a variety of names such as Introduction to Clinical Medicine, Doctoring, or The Practice of Medicine. In their most basic form, these courses introduce students to fundamental clinical skills such as medical interviewing, physical examination, oral presentations, and written documentation in a supervised environment.…”
Section: Introductionmentioning
confidence: 99%